Diffraction on an Aperture Located Between Media with Different Refractive Indices - Mkrtchyan, A. R.; Lalayan, A. A.; Eritsyan, H. S.; Margaryan, A. L.
Fraunhofer diffraction of a plane electromagnetic wave is considered on an aperture in an opaque screen located between two media with different refractive indices, as well as between vacuum and refractive material medium, in the presence and absence of birefringence. The angular distribution of the intensity of diffracted radiation is determined. The case of an anisotropic medium is also considered. Some peculiarities of diffraction in this formulation are revealed, in particular, including the nonreciprocity phenomenon. It is shown that the intensity of the diffracted wave depends on the refractive index of the medium into which the electromagnetic radiation penetrates. This leads to the possibility of creating new optical elements, the scope of which, in particular, can be the creation of alternative schemes for the light energy storage devices. An experimental study of the nonreciprocity phenomenon was carried out.
Keywords: Physics; Optics